PENGARUH KOMITMEN ORGANISASI, TIME BUDGET PRESSURE, LOCUS OF CONTROL, KINERJA AUDITOR, ETIKA AUDITOR DAN TURNOVER INTENTION TERHADAP PERILAKU DISFUNGSIONAL AUDIT (Studi Empiris Pada Kantor Akuntan Publik yang Berada di Kota Batam, Padang dan Pekanbaru ) - Efferida Septa Bella; Hardi Hardi; Wiguna Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine (1) organizational commitment to dysfunctional audit behavior (2) the effect of time budget pressure on dysfunctional audit behavior (3) the influence of locus of control on dysfunctional audit behavior (4) the effect of auditor performance on dysfunctional audit behavior (5) the effect of auditor ethics on dysfunctional audit behavior (6) the effect of turnover intention on dysfunctional audit behavior.The data used in this study is primary data with a questionnaire as an instrument. The method used for sample selection was purposive sampling. The population in this study was the Public Accounting Firm (KAP) located in Batam, Padang and Pekanbaru. The number of samples in this study were auditors who worked in 25 KAP distributed as many as 78 respondents and 69 questionnaires returned (88.46%). The data analysis technique used in this study was multiple linear regression analysis with the help of SPSS 23.0 for windows. The results of this study indicate that organizational commitment, time budget pressure, locus of control, auditor performance, auditor ethics, and turnover intention were proven to influence dysfunctional audit behavior.Keywords: organizational commitment, time budget pressure, locus of control, auditor performance, auditor ethics, turnover intention.